Ion Current Density Calculation of the Inductive Radio Frequency Ion Source - V.I. Voznyi; V.E. Storizhko; V.I. Miroshnichenko; D.P. Shulha (Журнал нано- та електронної фізики)
A radio-frequency (RF) inductive ion source at 27.12 MHz is investigated. With a global model of the argon discharge, plasma density, electron temperature and ion current density of the ion source is calculated in relation to absorbed RF power and gas pressure as a discharge chamber size changes. It is found that ion beam current density grows as the discharge chamber size decreases. Calculations show that in the RF source with a discharge chamber 30 mm in diameter and 35 mm long the ion current density is 40 mA/cm2 at 100 W of absorbed RF power and 7 mTorr of pressure, and agrees well with experimentally measured value of 43 mA/cm2. With decreasing discharge chamber diameter to 15 mm ion current density can reach 85 mA/cm2 at absorbed RF power of 100 W.